-3r+1=-17

Simple and best practice solution for -3r+1=-17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3r+1=-17 equation:


Simplifying
-3r + 1 = -17

Reorder the terms:
1 + -3r = -17

Solving
1 + -3r = -17

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + -3r = -17 + -1

Combine like terms: 1 + -1 = 0
0 + -3r = -17 + -1
-3r = -17 + -1

Combine like terms: -17 + -1 = -18
-3r = -18

Divide each side by '-3'.
r = 6

Simplifying
r = 6

See similar equations:

| -4(j-2)=8+j | | 7-2r=-7 | | 10x-2=5x-8 | | -2(-x+9)=24 | | 6p+3r-4p+7r=0 | | y-4x+4=-x+x^2 | | 3x=360+3y | | 7+3t=-(t-6) | | 8.4=8y+1.2 | | 180=20r | | 33-6X=3X+19 | | 1q+1=-5q-3+8q+4 | | (30y+4)+(8y^2-15y+4)=0 | | 1+1x+1y+1m=1 | | 72=5+20 | | 2x^2+11x-67=0 | | 1x-1.87x=13.92 | | -20=-8-f-f | | 14432432+324x=234234+42x-32y | | R+15=15 | | x=-7x+9+x(4x+6) | | h+7=2h+14-9 | | 20s=89 | | t(x)=2.4x^2+90.8x+1.59 | | 9x-2x=11 | | 12j-3(j-2)=33 | | 10=8+d+d+d+d | | 4x^2y-16x^2y^2-12xy=0 | | 3x+4x=140 | | 78=3d+12-d+4 | | 0=2.4x^2+90.8x+1.59 | | 4x+42-5x=2-8x+5 |

Equations solver categories